Hybrid and Blended Learning as the Emerging Educational Standard: An Analysis of Student Engagement and Outcomes - Kang, HS; Sutrisno, Djoko (Global Synthesis in Education Journal, 2026)
This study examined hybrid and blended learning as the emerging educational standard and its effects on student engagement and learning outcomes. Following the COVID-19 pandemic, these models have become routine practice in higher education. However, evidence of their sustained effectiveness remains limited. Drawing on the Community of Inquiry (CoI) framework and Self-Determination Theory (SDT), this research investigated the roles of teaching, social, and cognitive presence as well as the psychological needs of autonomy, competence, and relatedness in influencing behavioral, emotional, and cognitive engagement and academic performance. A convergent parallel mixed-methods design was used. Quantitative data were gathered from 428 undergraduate students via an online survey, supplemented by 32 semi-structured interviews. Data were analyzed using descriptive statistics, t-tests, correlations, multiple regression, and thematic analysis. Findings revealed moderately high student engagement (*M* = 4.05, *SD* = 0.68) and improved academic performance (mean GPA = 3.48). Hybrid learning produced significantly higher engagement than blended learning. The integrated CoI-SDT model accounted for 47% of the variance in engagement, with teaching presence (*β* = 0.39) and autonomy (*β* = 0.34) emerging as the strongest predictors. Qualitative themes emphasized flexibility, cognitive depth, and interpersonal connections. This study affirms that hybrid and blended learning can function effectively as the new educational norm when teaching presence and autonomy are deliberately supported. The findings offer valuable theory-driven insights and practical recommendations for higher education institutions